2021
DOI: 10.3233/jad-210628
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Mild Behavioral Impairment: A Functional Brain Connectivity Study Using Resting-State Functional Magnetic Resonance Imaging

Abstract: Background: Mild behavioral impairment (MBI) is associated with accelerated cognitive decline and greater risk of dementia. However, the neural correlates of MBI have not been completely elucidated. Objective: The study aimed to investigate the correlation between cognitively normal participants and participants with amnestic mild cognitive impairment (aMCI) using resting-state functional magnetic resonance imaging. Methods: The study included 30 cognitively normal participants and 13 participants with aMCI (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 53 publications
1
34
1
Order By: Relevance
“…Three studies also included patients with AD 39,45,48 . MBI was assessed using the MBI‐Checklist 52 in most studies 14,17,36,38,40,41,43–49,51 . Three studies used MBI criteria 2,11,12 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies also included patients with AD 39,45,48 . MBI was assessed using the MBI‐Checklist 52 in most studies 14,17,36,38,40,41,43–49,51 . Three studies used MBI criteria 2,11,12 .…”
Section: Resultsmentioning
confidence: 99%
“…The brain regions (hippocampus, parahippocampal gyrus, entorhinal cortex, and temporal lobe) identified as neural correlates of MBI 13,36,[39][40][41]43,44 (Figure 2) are known to show atrophy in the early stage of AD. 54 Tau burden in the entorhinal cortex and hippocampus has been linked to MBI in amyloid-positive NC, 17 but not in NC with an unknown amyloid status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 The only rs‐fMRI study of MBI in participants with NC and amnestic MCI reported no MBI‐associated FC changes within the DMN and SN but identified an association between MBI and dysfunction within the fronto‐parietal control network. 21 This study used a self‐report of MBI symptoms with infrequent endorsement of clinically significant MBI. Here, we aimed to investigate FC alterations in the DMN and SN in dementia‐free older adults with MBI compared to those without, using an informant‐rated MBI assessment.…”
Section: Introductionmentioning
confidence: 99%